Growth and Developmental Status of Children with Congenital Heart Disease - Nasiruzzaman, AHm; Hussain, MZ; Baki, MA; Tayeb, MA; Mollah, MN (Bangladesh Medical Journal, 2014)
Cardiac malformations ore responsible for malnutrition, which may range from mild under nutrition to severe failure to thrive (FTT). Developmental delay was also associated with congenital heart disease. The aim of the study was to evaluate the nutritional status and developmental status of children with congenital heart disease. This cross sectional study was done in the department of Paediatrics, BSMMU and Dhaka Shishu Hospital from March'08 to February'09. Children, age 1 month to 6 years with congenital heart disease confirmed by echocardiogram (both cyanotic and acyanotic heart disease) were included in this study. Total 50 children included in this study. Mean age of study patient was 3.04 (±2.01SD) years. Ventricular septal defects were found as leading number (36%). Tetralogy of Fallot was found in 26% cases. According to WHO standard 38% children from acyanotic and 16%/rom cyanotic heart disease were severely stunted. Ten percent children from acyanotic and 04% from cyanotic heart disease were severely wasted. Gross motor and fine motor delay was present in 60% and 54% of children. Forty four percent children had speech delay and social impairment was present in 32% children. Severe stunting was more common than wasting in this study. Gross motor and fine motor delay was found the main developmental problem. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18512 Bangladesh Medical Journal 2011 Vol.40(2): 54-57